A Review of an Urban Living Lab Initiative. Issue 3 (8th April 2021) - Tanda, Adriano; De Marco, Alberto
Abstract: In 2016 the city of Turin, Italy, launched the Torino Living Lab initiative. By using the urban Living Lab approach, with firms, public bodies, universities, and communities collaborating to co‐create innovation, Turin aims to encourage, attract, and foster a growing and inclusive innovation environment. This article describes the efforts that Turin has made to design the initiative and presents a structured methodology to assess its results. The expectations and objectives of the initiative's utilizers and the characteristics, impressions, habits, and behaviors of the citizens were collected before the initiative through a series of semi‐structured interviews and a survey. By comparing the obtained results with similar post‐mortem measurements, it is possible to assess the success of the initiative and evaluate its impacts. Finally, this study present interesting policy takeaways for cities wanting to implement urban Living Labs and identify best practices for their design, implementation, and management. 摘要: 2016年意大利都灵市启动了"都灵生活实验室"（Torino Living Lab）倡议。通过使用该倡议方法，与公司、公共机构、大学和社区协作创新，都灵旨在鼓励、吸引、培养一个不断成长的包容性创新环境。本文描述了都灵为设计该倡议所作的努力，并提出一项结构化方法以评估倡议结果。启动倡议之前，通过一系列半结构化访谈和一项调查，收集倡议使用者的期望和目标，以及公民的特征、印象、习惯和行为。通过将倡议结果和类似的研究分析加以比较，使"评估倡议成就并评价倡议影响"一事成为可能。最后，本研究为希望执行"生活实验室"方法的城市提出了新奇的政策意见，并就相关方法设计、执行及管理识别了最佳实践。 Resumen: En 2016, la ciudad de Turín, Italia, lanzó la iniciativa Torino Living Lab. Al utilizar el enfoque Urban Living Lab, con empresas, organismos públicos, universidades y comunidades que colaboran para co‐crear la innovación, Turín tiene como objetivo alentar, atraer y fomentar un entorno de innovación creciente e inclusivo. Este artículo describe los esfuerzos que ha realizado Turín para diseñar la iniciativa y presenta una metodología estructurada para evaluar sus resultados. Las expectativas y objetivos de los usuarios de la iniciativa y las características, impresiones, hábitos y comportamientos de los ciudadanos se recogieron antes de la iniciativa a través de una serie de entrevistas semiestructuradas y una encuesta. Al comparar los resultados obtenidos con mediciones post‐mortem similares, es posible evaluar el éxito de la iniciativa y evaluar sus impactos. Finalmente, este estudio presenta interesantes conclusiones de políticas para las ciudades que desean implementar Urban Living Labs e identificar las mejores prácticas para su diseño, implementación y gestión.